The Role of Digital Content in the Sustainability of the Food and Beverage (F&B) Industry - Arweni Arweni; Angga Hendharsa; Dami Dami (STKIP Singkawang, 2025)
The Food and Beverage (F&B) industry is experiencing dynamic growth, particularly in the coffee shop sector. The rapid expansion of coffee shops has intensified competition, influencing consumer purchase decisions. The evolving digital marketing landscape has enabled consumers to engage with digital content—namely Firm Generated Content (FGC) and User Generated Content (UGC)—which can enhance perceived value and subsequently drive purchasing behavior. Although both FGC and UGC have become increasingly prevalent, their distinct impacts merit further investigation. This study employed a survey method targeting individuals who have purchased coffee shop products in Pontianak. Quantitative data were collected and analyzed to support generalization through statistical evidence. A purposive sampling technique was used, requiring respondents to meet specific criteria. The analytical tool applied was Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) approach. The findings indicate that both FGC and UGC have a positive and significant influence on perceived value. Furthermore, FGC, UGC, and perceived value each positively and significantly affect purchase decisions. In terms of mediation, perceived value is proven to mediate the relationship between FGC and UGC with purchase decisions